Research on the teaching mode of university virtual laboratory based on component technology. (18th February 2022) - He, Shuling; Kong, Dejiang; Yang, Jingjun; Ma, Lingfa; Chang, Yuwei
In order to overcome the problems of low flexibility, low efficiency and non-reusability of laboratory teaching mode, a research method of university virtual laboratory teaching mode based on component technology is proposed. This method is composed of platform architecture module, platform operation module, routine project detection module and platform component module. Through the platform operation module scheduling module components to complete the experimental process; the components needed in the experimental process are detected, so that students can get more accurate experimental process and experimental results. By extracting the internal information of bean component, controlling and managing the dynamic results of the component after execution; using the component technology in swing graphics toolkit to realise the experiment process and result visualisation. The experimental results show that it can improve the utilisation rate of students' spare time, and the experimental practice ability can be improved by more than 15 points.